The letter hamzah: highlights of origin and background - Abd. Hamid, Felza Zulhibri; Yusof, Nor Hafizi; Ismail, Muhamad Fadlly; Abu Samah, Rozaimi (y Human Resource Management Academic Research Society (HRMARS), 2021)
Hamzah is a difficult letter in pronunciation compared to other letters because its point of articulation (makhraj) is located at the bottom part of the throat, the farthest compared to other points. Therefore, the symbol of hamzah also has a diverse background based on the hamzah letter identity, which has a concession (rukhsah) in the expression due to the difficulty of pronouncing it. The problem has caused confusion among the community to understand the scope of hamzah symbols found in the mushaf because the Muslim community, especially in Malaysia, is bound by the narration of Hafs bin Sulayman al-Kufi that does not reveal the change of the letter hamzah based on its identity. Therefore, the purpose of this study was to reveal the correct understanding of the scope of hamzah letters involving symbols, colours and vowel marks (lines or harakat) based on the history recorded by qurra’. This descriptive study discusses the views of qurra’ related to the letter hamzah, specifically involving symbols, colours and vowel marks (lines or harakat). All data were analysed using inductive and conductive methods. The findings show that the letter hamzah has a diverse background referring to its symbols, colours and vowel marks (lines or harakat). All these backgrounds cannot be realised within the community when they are still bound by the narration of Hafs bin Sulayman al-Kufi. If this understanding is not explained in detail to the public, it is worried that the community will be confused about the identity of the letter hamzah that is subject to various changes in all aspects, whether involving symbols in the mushaf or the variety of pronunciation based on ahruf al-Sab’ah. This study can also be an added value for teachers of the Quran in understanding the scope of the letter hamzah as one of the letters in the hija’iyyah letters.